A low threshold to ECG-gated repeat CTA reduces the risk of false-positive diagnosis of type A dissection in interhospital referrals: a case series study - Kornberger, Angela (Ther Clin Risk Manag, 2018)
BACKGROUND: False-positive diagnosis of acute Stanford type A aortic dissection (AAD) on computed tomography angiography (CTA) is still an issue and may lead to substantial consequences. Given that electrocardiography (ECG)-gated CTA provides greater diagnostic safety, it may be assumed that interhospital referrals with a diagnosis of AAD based on non-ECG-gated pre-referral CTA carry an elevated risk of false-positive diagnosis. PATIENTS AND METHODS: We reviewed a series of patients in whom a diagnosis of AAD based on non-ECG-gated pre-referral CTA was subsequently proven false by ECG-gated CTA. The artifacts that gave rise to the misdiagnosis, as well as the diagnostic pathways followed and the consequences of false-positive diagnosis were investigated. RESULTS: In 5 patients, ECG-gated repeat CTA revealed artifacts in the pre-referral scans that had led to false-positive diagnosis and referral for emergent surgery. In the first case, the patient proceeded to surgery. In 4 subsequent cases, ECG-gated CTA was ordered because a false-positive diagnosis was suspected. We found that ECG-gated CTA rather than echocardiography provided sufficient information to rule out AAD in each of these cases. Comparison between pre-referral non-ECG-gated scans and ECG-gated repeat CTA demonstrated the wide range of artifacts that may give rise to a diagnosis of AAD. CONCLUSION: Patient condition permitting, the threshold to ECG-gated repeat CTA should be low when doubt arises with regard to a diagnosis of AAD based on non-ECG-gated CTA in interhospital referrals.